ATLAS highlights: Recent results from ATLAS - Balek Petr (EPJ Web of Conferences)
The ATLAS experiment at the Large Hadron Collider encompasses a wide-ranging physics programme that includes various collision systems and centre-of-mass energies. These proceedings provide an overview of the recent ATLAS measurements regarding heavy ion collisions, heavy flavour production, and collective behaviour. The data utilized in the presented results were recorded during LHC Run 2 (2015–2018). The measurements can help to understand various physics phenomena from hard scatterings to soft processes, and from large systems to small systems.